NAMANGAN REGION BUILDING MAHSULOT OF WORK, PRODUCTION AND ITS TRADE - Tulqinjon Yusupjanovich Dadaboev; Azimova Muslima Kamoliddin daughter (American Journals, 2024)
This article describes Uzbekistan’s construction product work, production and sales of data, the export - import to the conditions of the study has been. Building products and features revealed specific aspects of the market. The construction industry on the development of xulom and suggestions given.
Keywords: Building products, eksport, import, marketing, sales, production, demand and offer.